Essential-oil pesticidal odorscapes: An exploratory multi-endpoint framework for profiling plant volatiles against walnut-associated stored-product beetles - Gabriel Omar Denett; Maria Rosa Rodriguez; Virginia L. Usseglio; Daniela Milagros Bracamonte; Tamara Elizabeth López; Jose Francisco Aranda Cano; María Paula Zunino; Jorge Omar Werdin Gonzalez; Diego Alejandro Sampietro; Nieves Carolina Comelli (Journal of Stored Products Research, 2027)

Integrative genomic and pathogenicity analyses reveal emerging Fusarium threats to cacao in Colombia - Lorena Dávila; Edwin Rodriguez; Alejandro Villabona-Gelvez; José C. Huguet-Tapia; Paola Zuluaga (Physiological and Molecular Plant Pathology, 2026)

Frequency matters: multi-year late-spring frosts severely reduce growth resilience of Nothofagus pumilio near Tierra del Fuego treeline - Sergio Piraino; Vladimir Matskovsky; Paolo Cherubini; Martín Ariel Hadad; Guillermo Martínez Pastur; Julián Rodriguez-Souilla; Fidel Alejandro Roig Juñent (Acta Oecologica, 2026)

Modeling the circulation in the Magdalena–Almejas Bay System forced by tides - Susana A. Rodriguez-Melgarejo; Alejandro F. Parés-Sierra; Ana Laura Flores-Morales (Continental Shelf Research, 2026)

Is seed dispersal a bottleneck for passive restoration in semi-arid pampean grasslands? A seed-trap experiment - Alois Fundneider; Diego Bambozzi; Dana Aylen Rodriguez; Maria Cecilia Scarfó; Camilla Wellstein; Alejandro Loydi (Plant Ecology, 2026)
Seed dispersal patterns at both species and community levels are widely discussed, but evidence from literature is often limited, especially for natural grasslands. Therefore, we investigated seed dispersal patterns in a natural grassland in Argentina to estimate the reliability of adjacent fields as propagule sources for target species (i.e., native forage species). We installed two different seed trap types (pot and sticky) at distances of 0, 0.1, 2, 4 and 9 m from the vegetation boundaries of an exclosure area, mainly dominated by perennial native grasses. Additionally, we surveyed the aboveground vegetation and estimated the potential seed production for every single species. In total we found 39 plant species in the aboveground vegetation of which 34 were observed to produce seeds and 29 were caught by the seed traps. Over time, species richness, seed density and similarity (Bray-Curtis, Jaccard) to the aboveground vegetation as well as the Shannon diversity index, generally increased. However, these increases were lower at greater distances from the field boundaries, regardless of seed trap type. Overall, pot traps were more effective at catching species and achieved a higher seed density than the sticky traps. Our results highlight the importance of field boundaries as potential sources of seeds for target species and their role in enhancing biodiversity in adjacent grasslands and arable land.

Corrigendum to ‘Clarification of olive juice by α-alumina microfiltration membranes with enhanced packing density’ [Innovative Food Science & Emerging Technologies Volume 102 June 2025 104031] - Alba Gutiérrez-Docio; Alejandro Ruiz-Rodriguez; Marin Prodanov (Innovative Food Science & Emerging Technologies, 2026)

Signal of phenotypic plasticity in the population dynamics of the crab Microcassiope xantusii across Pocillopora-dominated coral reefs - Sandra Rodriguez-Huezo; Manuel Ayon-Parente; Arizbeth Alonso-Dominguez; Fabian Alejandro Rodriguez-Zaragoza; Ignacio Caceres (Hydrobiologia, 2026)

Biocrust belt below the edge of a dying glacier in the Tropical Andes - Alejandro Salazar; Maria E. Gutiérrez-Lagoueyte; Ingibjörg S. Jónsdóttir; Isabel C. Barrio; Heiðrún I. Guðmundsdóttir; Emilio Rodriguez-Caballero; Adriana Sanchez (Alpine Botany, 2026)
On recently deglaciated terrain, soil instability can be a physical barrier limiting seedling establishment. Here we used a space-for-time approach to study the role of biological soil crust (biocrust) as soil surface stabilizer and facilitator of ecological succession along a glacier forefield chronosequence at the retreating Conejeras glacier in the Tropical Andes. We used the point-intercept method to estimate surface cover of plants, biocrust, bare ground and rocks, as well as soil surface roughness; and a field soil aggregate kit to estimate soil stability. As hypothesized, following a bare-ground stage near the edge of the glacier, the successional trajectory involved the development of a biocrust belt, including bryophytes and lichens, followed by an increasing vascular plant cover. The development of biocrust was accompanied by higher soil surface roughness and soil stability, which likely increased seed entrapment and seedling establishment. Our results suggest that the development of cyanobacterial-dominated biocrust at the forefield of the Conejeras glacier may favor the establishment of plants with large seeds, such as graminoids from the Festuca genus. Overall, our findings highlight the key role of biocrusts in the ecological dynamics that follow glacier melt in the Tropical Andes.

Application of a non-destructive methodology for determining the thickness of oblique cones - Daniel de Castro Maciel; Rafael Nunes Sigales; Naábia Kamila Gomes Guedes; Gilmar Cordeiro Silva; Alejandro Martins Rodriguez; Aline Soares Pereira (Next Research, 2026)

Valorization of Russian Sturgeon (Acipenser gueldenstaedtii) Processing Waste: Sustainable Enzymes for Biotechnological Applications Contributing to the Circular Economy - Clara Liébana; Juana Cristina del Valle; María Victoria Laitano; Ivana Soledad Friedman; Yamila Eliana Rodriguez; Alejandro Gabriel Perretta-Noschesi; Ignacio Quartiani-Zubieta; Analia Verónica Fernández-Gimenez (Circular Economy and Sustainability, 2026)

Population Genomic Analyses Reveal Geographic Structure in Rhizoctonia solani AG1 ‐ IA Isolates Associated With Agronomic Crops - Juanita Gil; Kensy Rodriguez‐Herrera; Vanina Castroagudin; Felipe Dalla Lana; Camila P. Nicolli; Xin‐Gen Zhou; Sara Thomas‐Sharma; Terry Spurlock; Jim C. Correll; Pierre Gladieux; Alejandro Rojas (Molecular Ecology, 2026)
Soilborne fungal pathogens threaten food security, but limited knowledge of their population biology, including genetic variability and population structure, hinders the development of effective strategies to prevent crop losses. Rhizoctonia solani AG‐1 is a significant soilborne pathogen worldwide, divided into subgroups based on host range and molecular diversity. Rhizoctonia solani AG1‐IA causes sheath blight in rice and aerial blight in soybean, two devastating diseases in these economically important crops. Rice and soybean are often grown in rotation, leading to the buildup of inoculum in the fields over cropping seasons. Monitoring the genetic variability and structure of R. solani AG1‐IA is critical to understand the population biology of the pathogen and aid in disease management practices, including the screening and development of new resistant cultivars. A total of 145 isolates of R. solani collected between 1993 and 2022 from different hosts and states in the USA were sequenced. The population genetic structure was inferred with clustering approaches based on approximately two million biallelic single nucleotide polymorphisms (SNPs). Rhizoctonia solani AG1‐IA showed relatively high genetic diversity and little departure from mutation‐drift equilibrium, suggesting that R. solani AG1‐IA is a well‐established, widespread pathogen with a stable demographic history in the USA. While populations had a clear geographic structure, they lacked host specialization, suggesting dispersal is mainly distance limited. Shared ancestry between populations and the discovery of clonal lineages, however, indicated recent connections between geographic areas. Our work provides valuable insights into the evolutionary history and population biology of R. solani AG1‐IA, offering a foundation for developing targeted management strategies and resistant crop varieties.

Dialogue between science, law, and traditional knowledge regarding global environmental problems - Manuel Alejandro Lizardi-Jiménez; Violeta Mendezcarlo Silva; María Suhey Tristán Rodriguez; Guillermo Luevano Bustamante; Gabriela Josefina Aguirre-García (Journal of Environmental Management, 2026)

Beneficial and potentially harmful compounds in edible mushrooms cultivated on substrates supplemented with algal wracks from Mar Menor lagoon seashore - Sara Figueredo; Rebeca Lavega; Luis Vázquez; Carlos García-Delgado; Francisco R. Marin; Alejandro Ruiz-Rodriguez; Cristina Soler-Rivas (Biocatalysis and Agricultural Biotechnology, 2026)

Bilateral retinal implants for improving visual restoration: a simulated bionic vision study - Pablo Rodriguez-Miguez; Pablo Ramon-Soria; Alejandro Barriga-Rivera (Medical & Biological Engineering & Computing, 2026)

Screening of enzyme-producing mushroom species able to grow on beach wracks from Mar Menor lagoon for their valorization - Sara Figueredo; Alejandro Ruiz-Rodriguez; Francisco R. Marín; Cristina Soler-Rivas (Journal of Applied Phycology, 2026)
Large amounts of algal beach wracks are accumulating on the shores of the Mar Menor lagoon due to its ecological imbalance. This biomass is collected and discarded in landfills without any added value. In an attempt to valorize this material, semi-solid media including dried algal wracks with or without prior dialysis, wheat straw and mycological malt extract agar (as control) were prepared to cultivate edible mushroom mycelia. The fungal enzymatic activities were analyzed to assess their potential to produce valuable enzymes for biotechnological applications, such as the food industry. The results indicated that Agaricus bisporus , Pleurotus ostreatus , Pleurotus ferulae , Flammulina velutipes , Hypsizygus tessulatus , Pholiota nameko , and Lentinula edodes could grow on both dialyzed and non-dialyzed algal wracks, while Ganoderma lucidum showed poor growth. Notably, most species produced more biomass on the algal wracks than on wheat straw, a standard substrate for mushroom cultivation. Non-dialyzed algal wracks stimulated the production (intramycelial) and secretion (extramycelial) of xylanases, particularly in L. edodes , F. velutipes , and H. tessulatus . When grown on dialyzed wracks, cellulase activity was mainly enhanced in P. ferulae , F. velutipes , and A. bisporus , and proteolytic activity was highest in F. velutipes and H. tessulatus . In contrast, the wracks were not suitable for inducing α-amylase activity. The production of laccases and peroxidases was more species-dependent than influenced by the tested substrate.

Impact of volcanic emissions on the air quality during the 2021 volcanic eruption of Tajogaite, La Palma: Implications for population exposure to volcanic pollutants - Julia Eychenne; Raphael Paris; Agnès Borbon; David Jessop; Mathieu Gouhier; Guillem Gisbert Pinto; Antoni Calafat; Aurélie Colomb; José-Luis Fernandez-Turiel; Vincent Gaussen; Clara Gorce; Séverine Moune; et al. (Science of The Total Environment, 2026)

Indirect exposure to organophosphate pesticides and its possible growth disorders in children of farmers in Northwest Mexico - Estefanía Ochoa-Ruiz; Aarón Israel Moreno-García; Daniel Alejandro Licea-Espinoza; Gisela Pineda-García; Krysta Paola Carranza-Ambriz; Kenya Karina Soto-Rodriguez; Arnold García-Ledezma; José Manuel Cornejo-Bravo; Ana Laura Martínez; Eleonora Mondani; Aracely Serrano-Medina (International Archives of Occupational and Environmental Health, 2026)
Purpose This study investigated the correlation between growth disorders and indirect pesticide exposure in children of farmers. Methods A cross-sectional study was conducted with 134 children of farmers occupationally exposed to organophosphate pesticides in the ejido Venustiano Carranza, an agricultural community in San Quintín, Baja California, Mexico. These children were compared with a control group of 56 unexposed children. Anthropometric measurements and biochemical analyses were performed in both groups to evaluate renal, hepatic, and nutritional profiles. Hormonal profiles were quantified using ELISA techniques. Cholinesterases are quantified using known colorimetric methods. Food security was also analyzed through a dietary diversity study, focusing on households. Results Indirectly exposed group showed a higher prevalence of stunting (18% vs. 16.4%) than controls. Food safety was adequate in both groups (X 2 = 1.88, p = 0.597). The indirectly exposure children showed significantly higher calcium levels (9.99 ± 0.63 mg/dL) and significant increases in liver enzymes AST and GGT ( p < 0.001). ALP was 1.5 times lower than in unexposed children ( p < 0.001), showing a strong association with exposure time ( p = 0.009). The indirectly exposed group showed lower GH and IGF-1 levels; 2.55 and 1.28 times lower than in controls, respectively. Children with indirect exposure showed a significant reduction in AChE (7211 ± 1917 vs. 8368 ± 213 U/L, p < 0.001) and an even greater decrease in BChE (6426 ± 1664 vs. 8025 ± 1462 U/L, p < 0.001). Conclusion This work demonstrates an association between environmental exposure to organophosphate pesticides and children's growth and provides crucial insights for future research and policymaking.

Governance Arrangements That Fit Social‐Ecological Context Are Associated With Fishery Sustainability - Mateja Nenadović; Alfredo Giron; Timothy Frawley; Adrian Munguia‐Vega; Kara E. Pellowe; Erica Ferrer; David Gill; Blanca González‐Mon; Andrew F. Johnson; Emilie Lindkvist; Fiorenza Micheli; Amy H. Weaver; et al. (Fish and Fisheries, 2026)
In many parts of the world, natural resources are primarily managed by governance arrangements at the local level. Those arrangements range from collective, such as cooperatives and associations, to individualistic, such as patrons and owner‐operators. A key question is how such arrangements influence resource use and associated social and ecological outcomes. We hypothesize that sustainable resource use is not associated with a specific governance arrangement, but instead that every type of arrangement has a certain set of social and ecological conditions under which sustainable resource use is feasible. This hypothesis was empirically investigated using fisheries landings data from Mexico. We found that sustainable resource use can be achieved through multiple governance arrangements provided that they are matched to appropriate social‐ecological contexts. Our findings help identify which governance arrangements are best suited to particular contexts and provide the initial building blocks for developing a theory of governance contextual fit in social‐ecological fishing systems.

Variability in cadmium stress and accumulation in quinoa: Potential role of crop domestication and selection in mediating differences in resilience and uptake - Alejandro Rodriguez-Sanchez; Martha Jimenez-Castaneda; Timothy Filley; David Brenner; Dennis Macedo; Victor H. Casa; Lori Hoagland (Science of The Total Environment, 2026)

Modulatory Role of Oral GHRP-6 in the Immune Response and Digestive Enzyme Function in Juvenile Tilapia (Oreochromis sp.) Challenged with Pseudomonas aeruginosa - Liz Mariam de Armas; Adrian Rodríguez-Gabilondo; Liz Hernández; Ernesto A. Quintana; Alejandro J. Campos; Noelia N. Pérez; Danielle Reyes; Antonio Morales; Osmany Rodrigo; Yaima González; Leandro Rodriguez-Viera; Mario Pablo Estrada; et al. (Fishes, 2026)
Aquaculture has been established as a sustainable alternative to traditional fisheries, which face challenges such as overexploitation and environmental degradation. However, disease outbreaks, often caused by poor farming conditions, pollution, and environmental stress, remain a major concern, leading to economic losses and increasing the risk of antibiotic resistance due to the overuse of antibiotics. Therefore, it is crucial to seek new strategies that improve fish health and well-being, preventing drug resistance and promoting sustainable practices. GHRP-6, a synthetic growth hormone-releasing peptide that mimics ghrelin, has shown potential immunostimulatory properties and feed efficiency in fish. In this study, we evaluated the effects of orally administered GHRP-6 in an oil-based formulation on juvenile tilapia (Oreochromis sp.) challenged or unchallenged with Pseudomonas aeruginosa. We assessed its influence on immune gene expression and digestive enzyme activity. The results demonstrated that GHRP-6 treatment significantly enhanced growth performance (weight and length), reduced in vivo bacterial load after infection, and modulated key genes related to innate and adaptive immunity in the gills, intestine and head kidney. In addition, our results demonstrated, for the first time, a direct link between a growth hormone secretagogue in fish and the modulation of specific enzyme activity in the gut following a bacterial challenge. These findings highlight the potential of GHRP-6 as a dietary immunomodulator and growth promoter in fish farming, offering a promising strategy to reduce antibiotic usage and promote more sustainable aquaculture practices.

Population dynamics and somatic production of burrowing shrimp assemblage in a Mexican estuary under ENSO-driven temperature fluctuations - Ignacio Caceres; Omar Hernando Avila-Poveda; Sandra Rodriguez-Huezo; Fabian Alejandro Rodriguez-Zaragoza; Manuel Ayon-Parente (Regional Studies in Marine Science, 2026)

Evaluating the NASA MPLNET Rain Masking Algorithm at Goddard Space Flight Center and Barcelona sites: Relevance to EarthCARE Cloud Profiling Radar Validation - Simone Lolli; Jasper R. Lewis; Ali Tokay; Gemine Vivone; James R. Campbell; Erica K. Dolinar; Michael Sïcard; Adolfo Comerón; Alejandro Rodriguez-Gomez; Constantino Muñoz-Porcar; Albert García-Benadí; Mireia Udina; et al. (Atmospheric Research, 2026)

Zinc adjuvant treatment in SARS-CoV-2: A randomized clinical trial - Silvia Gómez-Zorrilla; Elena Sendra; Juan Du; Mercé Espona; Alejandro Fierro-Villegas; Ana Siverio; Alicia Rodriguez-Alarcón; Silvia Castañeda; Inmaculada López Montesinos; Cristina Plata; Itziar Arrieta-Aldea; Jade Soldado-Folgado; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Association of Immunogenicity and Drug Exposure and the Importance of Target Engagement in ADA Development: A Clinical Case Study of Anti-SARS-CoV-2 Biotherapeutics - Susan C. Irvin; Samit Ganguly; Zhiqiang Wang; Zhongqing Will He; Marguerite Alejandro; Kaitlin Donohue; Chinnasamy Elango; Chris Gallo; Stephen Guttmann; Shawn Kalicharan; Kristina Kameron; James Laird; et al. (The AAPS Journal, 2025)
The administration of therapeutic proteins, such as monoclonal antibodies (mAbs) may result in the formation of anti-drug antibodies (ADA), but there is limited publicly available data for biotherapeutics with exogenous targets or with targets in low abundance systemically. ADAs can impact a biotherapeutic’s safety, efficacy, and pharmacokinetics, so evaluation of immunogenicity is required for all therapeutic proteins. This analysis sought to evaluate the immunogenicity of two mAbs against COVID-19, casirivimab (CAS) and imdevimab (IMD) administered as a cocktail (CAS + IMD), in multiple clinical trials across different participant populations to add knowledge about the immunogenicity risk of protein therapeutics against exogenous targets and the association between immunogenicity and drug exposure. Overall, the incidence of treatment-boosted and treatment-emergent ADAs and neutralizing antibodies in both disease treatment and prophylaxis settings were low (i.e., < 11%). Participants in these studies were followed for up to 225 days post-last dose. Over time, the incidence of treatment-emergent and treatment-boosted immunogenicity for each mAb increased, but the rates and titers remained low overall; when it developed, patients usually developed ADA to both mAbs. Frequency of administration, dose, and route of administration did not appear to impact rates of immunogenicity. Concentrations of CAS and IMD were similar between participants of different immunogenicity status, indicating immunogenicity of CAS and IMD had no impact on pharmacokinetics of these mAbs; there was also no observed impact on safety or efficacy. The data presented here may provide supportive information for assessing the immunogenicity risk of protein therapeutics with exogenous targets. Graphical Abstract

Influence of intensified upwelling on two different Corallina officinalis Linneo 1758 populations by exploring direct and indirect effects - Eva Rothäusler; Laura Ramajo; Lilly-Mo Kuhn; Fadia Tala; Alejandro B. Rodriguez-Navarro; Constanza Mena; Jorge Inostroza (Marine Environmental Research, 2025)

Linking within-host immune dynamics to between-host transmission and reinfection risk - Rodolfo Blanco-Rodriguez; Alejandro Anderson; Esteban Hernandez-Vargas (Journal of Theoretical Biology, 2025)

Biogenic nanoparticles: Synthesis, characterization, applications and scaling up limitations in water treatment - Alejandra Ortiz-Tirado; Luisa F. Medina-Ganem; Erick R. Bandala; Alain S. Conejo-Davila; Alejandro Vega-Rios; Ashantha Goonetilleke; Oscar M. Rodriguez-Narvaez (Journal of Environmental Chemical Engineering, 2025)

Interleukin-6 supplementation during in vitro maturation improves developmental competence of in vitro fertilized porcine oocytes - Manuela Garcia-Canovas; Adelina Lopez-Jara; Alejandro Gonzalez-Plaza; Inmaculada Parrilla; Heriberto Rodriguez-Martinez; Cristina Cuello; Emilio A. Martinez; Maria A. Gil (Theriogenology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Large language models as autonomous spacecraft operators in kerbal space program - Alejandro Carrasco; Victor Rodriguez-Fernandez; Richard Linares (Advances in Space Research, 2025)

Focused high-protein supplementation to ewes grazing Campos grassland during mid gestation improves maternal-fetal blood flow and skeletal muscle mass of the progeny - Javier Ithurralde; Ana Inés Trujillo; Ana Laura Astessiano; Mariana Garcia Kako Rodriguez; Ezequiel Jorge-Smeding; Danilo Fila; Carlos Batista; Alejandro Bielli; Raquel Pérez-Clariget (Livestock Science, 2025)

Clarification of olive juice by α-alumina microfiltration membranes with enhanced packing density - Alba Gutiérrez-Docio; Alejandro Ruiz-Rodriguez; Marin Prodanov (Innovative Food Science & Emerging Technologies, 2025)

Plant Domestication Alters the Nutritional Content of Guttation Droplets with Multi-Trophic Consequences - Pablo Urbaneja-Bernat; Paolo Salazar-Mendoza; Alejandro Tena; Joel González-Cabrera; Cesar Rodriguez-Saona (Journal of Chemical Ecology, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Mush system heterogeneities control magma composition and eruptive style on the Ocean Island of El Hierro, Canary Islands - Claudia Prieto-Torrell; Helena Albert; Meritxell Aulinas; Eloi González-Esvertit; Ilenia Arienzo; Guillem Gisbert; Valentin R. Troll; Jose-Luis Fernandez-Turiel; Alejandro Rodriguez-Gonzalez; Francisco-Jose Perez-Torrado (Contributions to Mineralogy and Petrology, 2025)
The study of recent eruptions in Ocean Islands (OIs) provides a unique window into the magma dynamics governing their plumbing systems and the mechanisms leading to eruptions. Here we present an integrated approach to unravel the dynamics of magmatic plumbing systems through detailed spatial, petrological, and geochemical characterisation of volcanic products ranging from crystal-rich ankaramitic lavas to trachytic tephras. We focus on the textural and geochemical spatial variations of 42 Holocene subaerial eruptions at the OI of El Hierro (Canary Islands), as well as on their petrogenetic significance for magmatic evolution and plumbing system architecture. Integrating geochemical data within fractional crystallisation modelling and mass balance calculations reveals that ankaramitic and porphyritic lavas with phenocryst modal abundances > 10 vol% result from melt extraction and crystal accumulation. Aphyric to sub-aphyric eruption products and porphyritic lavas with phenocryst modal abundances < 10 vol% usually follow fractional crystallisation trajectories that start at ~ 10 wt% MgO. Periodic extraction of evolved melt from crystal mushes likely led to the occurrence of minor trachytic eruptions, which are difficult to reconcile with simple closed system fractional crystallisation trends. A complex, heterogeneous crustal mush system beneath El Hierro is, in fact, the most reliable scenario to explain the wide range of textures, whole-rock and mineral compositions, and the overall surface distribution of vents and eruptive styles displayed by the Holocene volcanism on the island. Our integrated findings highlight the importance of a combined field, petrological, and geochemical study to decipher plumbing system dynamics of OI magmatism. The results allow us to put forward an updated conceptual model of the current plumbing architecture of El Hierro’s volcanic system during the Holocene.

Venom variation and ontogenetic changes in the Crotalus molossus complex: Insights into composition, activities, and antivenom neutralization - Miguel Borja; Gamaliel Castañeda-Gaytán; Alejandro Alagón; Jason L. Strickland; Christopher L. Parkinson; Areli Gutiérrez-Martínez; Bruno Rodriguez-López; Vanessa Zarzosa; Bruno Lomonte; Anthony J. Saviola; Julián Fernández; Cara F. Smith; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Platelet Analysis in the Thrombus Plus Serum BNP for Detecting Clot-Related Atrial Fibrillation. Results From the ITACAT Multicentric Registry - Jorge Pagola; Jesus Juega; Laura Dorado; Maria Hernandez-Perez; Carlos Lazaro; Alvaro Garcia-Tornel; Marta Olive; Manuel Requena; Marta Rubiera; Marian Muchada; Noelia Rodriguez-Villatoro; David Rodriguez-Luna; et al. (Translational Stroke Research, 2025)

A new opportunity for N-acetylcysteine. An outline of its classic antioxidant effects and its pharmacological potential as an epigenetic modulator in liver diseases treatment - Marina Galicia-Moreno; Hugo Christian Monroy-Ramirez; Fernando Caloca-Camarena; Scarlet Arceo-Orozco; Pablo Muriel; Ana Sandoval-Rodriguez; Jesús García-Bañuelos; Alejandro García-González; José Navarro-Partida; Juan Armendariz-Borunda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Exploring the effects of cellulose sources on silver reduction and the bacterial removal of nanocellulose-based hydrogel beads - Diego Gomez-Maldonado; Brieanne R. Dickson; Gabriel Au; Michael J. Bortner; Mi Li; Eduardo Espinosa; Alejandro Rodriguez; Brendan Higgins; Maria S. Peresin (Carbohydrate Polymers, 2025)

Unraveling the ozone impact and oxidative stress on the nervous system - Paola Rodriguez; Alejandro López-Landa; Héctor Romo-Parra; Moisés Rubio-Osornio; Carmen Rubio (Toxicology, 2024)

Integration of microbial bioreactors and Lemna minor cultivation for sustainable treatment of dairy processing wastewater - Éamonn Walsh; Lekha Menon Margassery; Alejandro Rodriguez-Sanchez; David Wall; Paul Bolger; Marcel A.K. Jansen; Niall O'Leary (Journal of Water Process Engineering, 2024)

Effect of water stress and temperature on seed germination of five perennial grass species of the semi-arid Pampas - María Cecilia Scarfó; Dana Aylen Rodriguez; Clara Milano; Alejandro Loydi (Journal of Arid Environments, 2024)

Editorial overview: Parasites/parasitoids/biological control (2024) — research advances on plant-derived food sources in biological control - Pablo Urbaneja-Bernat; Alejandro Tena; Cesar Rodriguez-Saona (Current Opinion in Insect Science, 2024)

Vitrification of pig embryos dysregulates the microRNA transcriptome profile - Cristina Cuello; Alejandro González-Plaza; Josep M. Cambra; Manuela Garcia-Canovas; Inmaculada Parrilla; Heriberto Rodriguez-Martinez; Maria A. Gil; Emilio A. Martinez (Theriogenology, 2024)

Anti-oomycete activity and plant growth promoting properties of avocado fungal endophytes - Emma I. Nieves-Campos; Alejandro Méndez-Bravo; Yareli Pérez-Bautista; Jesús Llanderal-Mendoza; Edgar Guevara-Avendaño; Itzel A. Solís-García; Nayeli A. Diyarza-Sandoval; Silvia M. Contreras-Ramos; Jacobo Rodriguez-Campos; Alfonso Méndez-Bravo; Frédérique Reverchon (Rhizosphere, 2024)

High contribution of an invasive macroalgae species to beach wrack CO2 emissions - Iván Franco Rodil; Valle Perez Rodriguez; Alejandro Bernal-Ibáñez; Mauro Pardiello; Federica Soccio; Ignacio Gestoso (Journal of Environmental Management, 2024)

Mechanical properties of wax-oleogels: Assessing their potential to mimic commercial margarine functionality under small and large deformations - Erwin R. Werner-Cárcamo; Yasamin Soleimaniam; Braulio A. Macias-Rodriguez; Mónica Rubilar; Alejandro G. Marangoni (Food Research International, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

A metabolomics perspective on the effect of environmental micro and nanoplastics on living organisms: A review - Leilei Zhang; Pascual García-Pérez; Barbara Muñoz-Palazon; Alejandro Gonzalez-Martinez; Luigi Lucini; Alejandro Rodriguez-Sanchez (Science of The Total Environment, 2024)

Total CO2 budget estimate and degassing dynamics for an active stratovolcano: Turrialba Volcano, Costa Rica - Kate M. Nelson; Christofer Jiménez; Chad D. Deering; Maarten J. de Moor; Joshua M. Blackstock; Stephen P. Broccardo; Florian M. Schwandner; Joshua B. Fisher; Snehamoy Chatterjee; Guillermo Alvarado Induni; Alejandro Rodriguez; Doménicca Guillén Pachacama; et al. (Journal of Volcanology and Geothermal Research, 2024)

Treatment of dairy wastewater using intermittent-aeration sequencing batch reactor at pilot-scale - Alejandro Rodriguez-Sanchez; Beatriz Gil-Pulido; Peter Leonard; William Finnegan; Xinmin Zhan; Alan D.W. Dobson; Niall O'Leary (Bioresource Technology Reports, 2024)

Development and growth of bovine calves demi-embryos - Amada E. Ynsaurralde-Rivolta; Andres Rogberg-Muñoz; Sebastian Lopez-Valiente; Sebastian Maresca; Alejandro Rodriguez; Carlos Munar; Sebastian Munilla-Leguizamón; Franco A. Dellavalle; Daniel Salamone (Animal Reproduction Science, 2024)

An insect’s energy bar: the potential role of plant guttation on biological control - Pablo Urbaneja-Bernat; Alejandro Tena; Joel González-Cabrera; Cesar Rodriguez-Saona (Current Opinion in Insect Science, 2024)

Crustal structure of the Western Azuero Peninsula, Panama: Insights into the structure of accretionary complexes and forearc ophiolites - Carolina Ortiz-Guerrero; Camilo Montes; David W. Farris; Catalina Agudelo; Margarita Ariza Acero; Juliana Ayala; Jose David Avellaneda; Alejandro Cortes-Calderon; Esteban Gaitan; Sebastian Garzon; Daniel Gongora-Blanco; Nubia Andrea Jara; et al. (International Geology Review, 2024)

Effects of meteo-oceanographic conditions on the weathering processes of oil spills in northeastern Brazil - Humberto L. Varona; Carlos Noriega; Amilcar E. Calzada; Carmen Medeiros; Alexander Lobaina; Alejandro Rodriguez; Dayron Chang; Dailin Reyes; Julia Araujo; Marcus Silva; Marcio das Chagas Moura; Moacyr Araujo (Marine Pollution Bulletin, 2024)

Flathead grey mullet (Mugil cephalus) juveniles exhibit consistent proactive and reactive stress coping styles - Joel Fitzgerald Linares-Cordova; Sonia Rey-Planellas; Anaïs Boglino; Jessica A. Jimenez-Rivera; Neil J. Duncan; Gustavo Alejandro Rodriguez-Montes de Oca; Zohar Ibarra-Zatarain (Aquaculture, 2024)

Corrigendum to “JM-20 treatment prevents neuronal damage and memory impairment induced by aluminum chloride in rats” [Neurotoxicology 87 (2021) 70–85] - Maylin Wong-Guerra; Yanay Montano-Peguero; Jeney Ramírez-Sánchez; Javier Jiménez-Martin; Luis Arturo Fonseca-Fonseca; Daniela Hernández-Enseñat; Yasmine Nonose; Odalys Valdés; Abel Mondelo-Rodriguez; Yaquelin Ortiz-Miranda; Gretchen Bergado; Tania Carmenate; et al. (NeuroToxicology, 2023)

Why are you hitting yourself? Whole-exome sequencing diagnosis of monogenic autoimmunity - Lina M. Castano-Jaramillo; Francisco Rivas Larrauri; Selma C. Scheffler-Mendoza; Alonso Gutierrez-Hernandez; Juan Carlos Bustamante Ogando; Paulina Colin; Margarita Ortega Cisneros; Sandra Rajme-López; Edgar Alejandro Medina-Torres; Laura Berron Ruiz; Ana Luisa Rodriguez-Lozano; Sara Elva Espinosa Padilla; et al. (Journal of Genetics, 2023)

Ontogenetic change in the venom composition of one Mexican black-tailed rattlesnake (Crotalus molossus nigrescens) from Durango, Mexico - Miguel Borja; Edgar Neri-Castro; Arelí Gutiérrez-Martínez; Richard Bledsoe; Vanessa Zarzosa; Bruno Rodriguez-López; Jason L. Strickland; Jorge Becerra-López; Sara Valenzuela-Ceballos; Christopher L. Parkinson; Alejandro Alagón; Gamaliel Castañeda-Gaytán (Toxicon, 2023)

Financial and Operational Feasibility Pilot of a Medically Tailored Meal Program - W. Phillips; S. Geneva; M. Yepes-Rios; M. Alejandro-Rodriguez; J. Evans; R. Miles (Journal of the Academy of Nutrition and Dietetics, 2023)

Impressions of the scientific training in fishery and aquaculture biotechnology in Mar del Plata, Argentina: Communication, networking, and multidisciplinary research - Ângelo Paggi Matos; Andressa Coimbra Pereira; Alejandro Perretta; Patricia Romero-Murillo; Luciana Melisa Del Gobbo; Emily Sol Garcia Martinez; Samuel Hilevski; Lucas Roberto Sepúlveda; Agustín Fernando Boan; Daniela Sartoni; Daiana Yanel Pereyra; Lucia García Martínez; et al. (Aquaculture, 2023)

Cryotop vitrification of large batches of pig embryos simultaneously provides excellent postwarming survival rates and minimal interference with gene expression - Alejandro Gonzalez-Plaza; Josep M. Cambra; Manuela Garcia-Canovas; Inmaculada Parrilla; Maria A. Gil; Emilio A. Martinez; Heriberto Rodriguez-Martinez; Cristina A. Martinez; Cristina Cuello (Theriogenology, 2023)

LIPRNAseq: a method to discover lipid interacting RNAs by sequencing - Andrea Bayona-Hernandez; Susana Guerra; Irma Angélica Jiménez-Ramirez; Martin Sztacho; Pavel Hozak; Luis Carlos Rodriguez-Zapata; Alejandro Pereira-Santana; Enrique Castaño (Molecular Biology Reports, 2023)

Citizen Science Improves the Known and Potential Distribution of a Strong Wetland Invader: Implications for Niche Modeling and Invasion Management - Paula Gervazoni; Gianmarco Minuti; Daniela Fuentes-Rodriguez; Julie Coetzee; Alejandro Sosa; Lara Sabater; Celeste Franceschini (Environmental Management, 2023)

Carrot genotypes differentially alter soil bacterial communities and decomposition of plant residue in soil - Narda J. Triviño; Alejandro Rodriguez-Sanchez; Timothy Filley; James J. Camberato; Micaela Colley; Phillip Simon; Lori Hoagland (Plant and Soil, 2023)
Purpose Farmers need alternative approaches to manage nitrogen (N) that meet crop needs while reducing loss to the environment. Identifying crop genotypes that promote decomposition of organic materials and understanding the potential mechanisms responsible could help address this challenge. Consequently, we aimed to 1) determine whether carrot genotypes differ in their potential to facilitate organic matter decomposition in soil, and 2) identify bacterial taxa that are stimulated by carrot roots, and thus could play a role in these processes. Methods We grew five genotypes expected to differ in N use efficiency in a nutrient-poor soil amended with 15 N-enriched corn residue, tracked changes in carbon (C) and N pools, quantified microbial activity and bacterial community composition, and predicted the potential expression of microbial genes involved in soil C and N cycles. Results Experimental genotype 8503 had the greatest capacity to promote decomposition of corn residues. This genotype had the highest % of N from the corn residue in its taproots and on average, promoted higher b-glucosidase activity in soils. Distinct bacterial communities from the families Micromonosporaceae , Chromatiaceae , and Rhodospirillaceae were also enriched in the soils of genotypes like 8503 that were most effective in obtaining N from the corn residue, and this was correlated with greater potential expression of genes responsible for β-glucosidase and nitrification activity. Conclusions Carrot genotypes do differ in their potential to alter soil bacterial communities and stimulate microbially-mediated decomposition of organic materials indicating that it may be possible to begin selecting for this important trait.

Comparison of the 7-day CO-Synch and 8-day estradiol-based protocols for estrus synchronization and timed artificial insemination in suckled Bos taurus cows - Alejandro M. Rodriguez; Sebastian Maresca; Sebastian López-Valiente; María G. Bilbao; Karen D. Moran; Julián A. Bartolome; Scott L. Pratt; Nathan M. Long (Theriogenology, 2023)

Monocyte-to-Lymphocyte Ratio in Clot Analysis as a Marker of Cardioembolic Stroke Etiology - Jesús Juega; Carlos Palacio-Garcia; Maite Rodriguez; Matias Deck; David Rodriguez-Luna; Manuel Requena; Álvaro García-Tornel; Noelia Rodriguez-Villatoro; Marta Rubiera; Sandra Boned; Marian Muchada; Marc Ribo; et al. (Translational Stroke Research, 2022)

In vivo subchronic effects of ciguatoxin-related compounds, reevaluation of their toxicity - Sandra Raposo-García; Andrea Boente-Juncal; Mercedes Rodriguez-Vieytes; Mercedes Camiña; Celia Costas; Alejandro Cao; M. Carmen Louzao; Manuel Cifuentes; Carmen Vale; Luis M. Botana (Archives of Toxicology, 2022)
Ciguatoxins are marine compounds that share a ladder-shaped polyether structure produced by dinoflagellates of the genus Gambierdiscus and Fukuyoa , and include maitotoxins (MTX1 and MTX3), ciguatoxins (CTX3C) and analogues (gambierone), components of one of the most frequent human foodborne illness diseases known as ciguatera fish poisoning. This disease was previously found primarily in tropical and subtropical areas but nowadays, the dinoflagellates producers of ciguatoxins had spread to European coasts. One decade ago, the European Food Safety Authority has raised the need to complete the toxicological available data for the ciguatoxin group of compounds. Thus, in this work, the in vivo effects of ciguatoxin-related compounds have been investigated using internationally adopted guidelines for the testing of chemicals. Intraperitoneal acute toxicity was tested for maitotoxin 1 at doses between 200 and 3200 ng/kg and the acute oral toxicity of Pacific Ciguatoxin CTX3C at 330 and 1050 ng/kg and maitotoxin 1 at 800 ng/kg were also evaluated showing not effects on mice survival after a 96 h observation period. Therefore, for the following experiments the oral subchronic doses were between 172 and 1760 ng/kg for gambierone, 10 and 102 ng/kg for Pacific Ciguatoxin CTX3C, 550 and 1760 ng/kg for maitotoxin 3 and 800, 2560 and 5000 ng/kg for maitotoxin 1. The results presented here raise the need to reevaluate the in vivo activity of these agents. Although the intraperitoneal lethal dose of maitotoxin 1 is assumed to be 50 ng/kg, without chemical purity identifications and description of the bioassay procedures, in this work, an intraperitoneal lethal dose of 1107 ng/kg was obtained. Therefore, the data presented here highlight the need to use a common procedure and certified reference material to clearly establish the levels of these environmental contaminants in food.

Regulatory mechanisms behind the phenotypic plasticity associated with Setaria italica water deficit tolerance - Vanessa Fuentes Suguiyama; Jae Diana Paredes Rodriguez; Tatiane Cristina Nicomedio dos Santos; Bruno Silvestre Lira; Luis Alejandro de Haro; João Paulo Naldi Silva; Eduardo Leite Borba; Eduardo Purgatto; Emerson Alves da Silva; Nicolas Bellora; Fernando Carrari; Danilo da Cruz Centeno; et al. (Plant Molecular Biology, 2022)

The Colombian geochronological database (CGD) - Andres F. Rodriguez-Corcho; Yamirka Rojas-Agramonte; Johana A. Barrera-Gonzalez; Maria P. Marroquin-Gomez; Sarah Bonilla-Correa; David Izquierdo-Camacho; Sofia M. Delgado-Balaguera; David Cartwright-Buitrago; Maria D. Muñoz-Granados; William G. Carantón-Mateus; Alejandro Corrales-García; Andrés F. Laverde-Martinez; et al. (International Geology Review, 2022)

Predicting Atrial Fibrillation with High Risk of Embolization with Atrial Strain and NT-proBNP - Jorge Pagola; Jesus Juega; Jaume Francisco-Pascual; Alejandro Bustamante; Anna Penalba; Elena Pala; Maite Rodriguez; Mercedes De Lera-Alfonso; Juan F. Arenillas; Juan Antonio Cabezas; Francisco Moniche; Reyes de Torres; et al. (Translational Stroke Research, 2021)

Evaluating the nitrogen-contaminated groundwater treatment by a denitrifying granular sludge bioreactor: effect of organic matter loading - Barbara Muñoz-Palazon; Alejandro Rodriguez-Sanchez; Miguel Hurtado-Martinez; Jesús Gonzalez-Lopez; Riku Vahala; Alejandro Gonzalez-Martinez (Environmental Science and Pollution Research, 2021)

An intrapopulational study of organic compounds and biomechanical properties of the shell of the Antarctic bivalve Laternula elliptica (P. P. King, 1832) at King George Island - M. Roberto García-Huidobro; María Josefina Poupin; Cristóbal Urrutia; Alejandro B. Rodriguez-Navarro; Christian Grenier; Juan F. Vivanco; Laura Ramajo; Isabel Benjumeda; Nelson A. Lagos; Marco A. Lardies (Polar Biology, 2021)

Molecular characterization of KPC-2-producing Klebsiella pneumoniae ST258 isolated from bovine mastitis - Jesús Silva-Sanchez; Humberto Barrios-Camacho; Emmanuel Hernández-Rodriguez; Josefina Duran-Bedolla; Alejandro Sanchez-Perez; Luary C. Martínez-Chavarría; Juan Xicohtencatl-Cortes; Rigoberto Hernández-Castro; Ulises Garza-Ramos (Brazilian Journal of Microbiology, 2021)

The influence of natural fire and cultural practices on island ecosystems: Insights from a 4,800 year record from Gran Canaria, Canary Islands - Cesare Ravazzi; Michela Mariani; Constantino Criado; Lorena Garozzo; Agustín Naranjo‐Cigala; Francisco J. Perez‐Torrado; Roberta Pini; Alejandro Rodriguez‐Gonzalez; Sandra Nogué; Robert J. Whittaker; José María Fernández‐Palacios; Lea de Nascimento (Journal of Biogeography, 2021)
Aim Long‐term ecological data provide a stepped frame of island ecosystem transformation after successive waves of human colonization, essential to determine conservation and management baselines. However, the timing and ecological impact of initial human settlement on many islands is still poorly known. Here, we report analyses from a 4800‐year sedimentary sequence from Gran Canaria (Canary Islands), with the goal of disentangling forest responses to natural fire from early human pressure on the island. Location La Calderilla, a volcanic maar caldera at 1,770 m a.s.l. on Gran Canaria. Taxon Plants and fungi. Methods A core from the caldera infill was analysed for sediment properties, pollen, micro‐ and macrocharcoal, with radiocarbon and biochronology dating. Fossil data were statistically zoned and interpreted with the help of cross‐correlation and ordination analyses. Surface samples and a pollen–vegetation training set were used as modern analogues for vegetation reconstruction. Results Before human settlement (4,800–2,000 cal. yr bp ), pine ( Pinus canariensis ) pollen dominated. Extensive dry pine forests characterized the highlands, although with temporary declining phases, followed by prompt (sub‐centennial scale) recovery. Towards 2,280 cal. yr bp there was a shift to open vegetation, marked by an increase in coprophilous spores. Coincidental with independent evidence of human settlement in the pine belt (2,000–470 cal. yr bp ) there was a decline of pine and a peak in charcoal. Following historic settlement (470–0 cal. yr bp ), pollen producers from anthropogenic habitats, secondary vegetation and coprophilous fungi increased in abundance, reflecting higher pressure of animal husbandry and farming. Modern moss polsters reflect extensive reforestation since 1950 ce (Common Era). Main conclusions From 4,800 cal. yr bp, the pristine vegetation covering the Gran Canaria highlands was a mosaic of dry pine forests and open vegetation. The pine forests sustained intense fires, which may well have promoted habitat diversity. Human interference was initiated around 2,280 cal. yr bp probably by recurrent cultural firing and animal husbandry, triggering a steady trend of forest withdrawal and expansion of grasses and scrubs, until the final disappearance of the pine forest locally in the 20th century. Grasslands were found to be of ancient cultural origin in the summit areas of Gran Canaria, although they underwent an expansion after the Castilian Conquest.

The SoNAP gene from sugarcane (Saccharum officinarum) encodes a senescence-associated NAC transcription factor involved in response to osmotic and salt stress - Evelyn A. Carrillo-Bermejo; Samuel David Gamboa-Tuz; Alejandro Pereira-Santana; Miguel A. Keb-Llanes; Enrique Castaño; Luis Joel Figueroa-Yañez; Luis C. Rodriguez-Zapata (Journal of Plant Research, 2020)

The alien invasive yellow flag (Iris pseudacorus L.) in Argentinian wetlands: assessing geographical distribution through different data sources - Paula Gervazoni; Alejandro Sosa; Celeste Franceschini; Julie Coetzee; Ana Faltlhauser; Daniela Fuentes-Rodriguez; Agustina Martínez; Martin Hill (Biological Invasions, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Dense Mytilus Beds Along Freshwater-Influenced Greenland Shores: Resistance to Corrosive Waters Under High Food Supply - Carlos M. Duarte; Alejandro B. Rodriguez-Navarro; Antonio Delgado-Huertas; Dorte Krause-Jensen (Estuaries and Coasts, 2020)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Adenovirus 5 produces obesity and adverse metabolic, morphological, and functional changes in the long term in animals fed a balanced diet or a high-fat diet: a study on hamsters - Daniel A. Montes-Galindo; Ana C. Espiritu-Mojarro; Valery Melnikov; Norma A. Moy-López; Alejandro D. Soriano-Hernandez; Hector R. Galvan-Salazar; Jorge Guzman-Muñiz; Jose Guzman-Esquivel; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; Brenda Paz-Michel; Sergio A. Zaizar-Fregoso; et al. (Archives of Virology, 2019)

Influence of salinity cycles in bioreactor performance and microbial community structure of membrane-based tidal-like variable salinity wastewater treatment systems - Alejandro Rodriguez-Sanchez; Juan Carlos Leyva-Diaz; Barbara Muñoz-Palazon; Jose Manuel Poyatos; Jesus Gonzalez-Lopez (Environmental Science and Pollution Research, 2019)

Validity of Skin, Oral and Tympanic Temperatures During Exercise in the Heat: Effects of Wind and Sweat - Ricardo Morán-Navarro; Javier Courel-Ibáñez; Alejandro Martínez-Cava; Elena Conesa-Ros; Alejandro Sánchez-Pay; Ricardo Mora-Rodriguez; Jesús G. Pallarés (Annals of Biomedical Engineering, 2019)

Research and management as key drivers in the evolution of the fishery of striped venus (Chamelea gallina) in the Spanish waters of the Gulf of Cádiz - Luis Silva Caparro; Marina Delgado Fernández; Miguel Cojan Burgos; Ana Rodriguez-Rua Franch; Sara Román Romero; Raimundo Blanco Pérez; Esperanza García Sumariva; Alejandro Terrón Singler; Javier Collado Vallejo (Frontiers in Marine Science, 2019)

The fishery of the striped venus Chamelea gallina (Linnaeus, 1758) in the Spanish waters of the Gulf of Cadiz (SW Spain): distribution and abundance of target and commercial discarded species. - Miguel Cojan Burgos; Luis Silva Caparro; Ana Rodriguez-Rua Franch; Raimundo Blanco Pérez; Sara Roman Moreno; Esperanza Garcia Sumariva; Alejandro Garcia Gomez; MarinaL Delgado Fernández; Alejandro Terron Singler; Javier Collado Vallejo; Rafael Gálvez César; Francisco Morales Mazo (Frontiers in Marine Science, 2019)

Maximum Influent Salinity Affects the Diversity of Mineral-Precipitation-Mediating Bacterial Communities in Membrane Biofilm of Hybrid Moving Bed Biofilm Reactor-Membrane Bioreactor - Alejandro Rodriguez-Sanchez; Barbara Muñoz-Palazon; Miguel Hurtado-Martinez; Maria Angustias Rivadeneyra; Jose Manuel Poyatos; Jesus Gonzalez-Lopez (Water, Air, & Soil Pollution, 2018)

Linear and nonlinear rheological behavior of fat crystal networks - Braulio A. Macias-Rodriguez; Alejandro A. Marangoni (Critical Reviews in Food Science and Nutrition, 2018)

Expression and biochemical characteristics of two different aldosterone receptors in both healthy and dilated cardiomyopathy dog heart tissue - Alejandro R. Reynoso Palomar; Moncerrat Rodriguez Bravo; Abel E. Villa Mancera; Carlos J. Mucha (Veterinary Research Communications, 2017)

Detection of comammox bacteria in full-scale wastewater treatment bioreactors using tag-454-pyrosequencing - Alejandro Gonzalez-Martinez; Alejandro Rodriguez-Sanchez; M. C. M van Loosdrecht; Jesus Gonzalez-Lopez; Riku Vahala (Environmental Science and Pollution Research, 2016)

Biomineralization changes with food supply confer juvenile scallops ( Argopecten purpuratus ) resistance to ocean acidification - Laura Ramajo; Núria Marbà; Luis Prado; Sophie Peron; Marco A. Lardies; Alejandro B. Rodriguez‐Navarro; Cristian A. Vargas; Nelson A. Lagos; Carlos M. Duarte (Global Change Biology, 2016)
Future ocean acidification ( OA ) will affect physiological traits of marine species, with calcifying species being particularly vulnerable. As OA entails high energy demands, particularly during the rapid juvenile growth phase, food supply may play a key role in the response of marine organisms to OA . We experimentally evaluated the role of food supply in modulating physiological responses and biomineralization processes in juveniles of the Chilean scallop, Argopecten purpuratus, that were exposed to control ( pH ~ 8.0) and low pH ( pH ~ 7.6) conditions using three food supply treatments (high, intermediate, and low). We found that pH and food levels had additive effects on the physiological response of the juvenile scallops. Metabolic rates, shell growth, net calcification, and ingestion rates increased significantly at low pH conditions, independent of food. These physiological responses increased significantly in organisms exposed to intermediate and high levels of food supply. Hence, food supply seems to play a major role modulating organismal response by providing the energetic means to bolster the physiological response of OA stress. On the contrary, the relative expression of chitin synthase, a functional molecule for biomineralization, increased significantly in scallops exposed to low food supply and low pH , which resulted in a thicker periostracum enriched with chitin polysaccharides. Under reduced food and low pH conditions, the adaptive organismal response was to trade‐off growth for the expression of biomineralization molecules and altering of the organic composition of shell periostracum, suggesting that the future performance of these calcifiers will depend on the trajectories of both OA and food supply. Thus, incorporating a suite of traits and multiple stressors in future studies of the adaptive organismal response may provide key insights on OA impacts on marine calcifiers.

Impact of methionine on a partial-nitritation biofilter - Alejandro Gonzalez-Martinez; Alejandro Rodriguez-Sanchez; Maria Jesus Garcia-Ruiz; Francisco Osorio; Jesus Gonzalez-Lopez (Environmental Science and Pollution Research, 2016)

Displacement of Br− and P22 in a Wetland Environment - Juan A. Vidales-Contreras; Humberto Rodriguez-Fuentes; Alejandro I. Luna-Maldonado; Jesus J. Hernandez-Escareño (Water, Air, & Soil Pollution, 2015)

Salbutamol but not ipratropium abolishes leukotriene D4-induced gas exchange abnormalities in asthma - Barbro Dahlén; Federico P Gómez; Alejandro Casas; Peter H Howarth; Sven-Erik Dahlén; Robert Rodriguez-Roisin (European Journal of Clinical Pharmacology, 2012)

Detection of sequences from a potentially novel strain of cell fusing agent virus in Mexican Stegomyia (Aedes) aegypti mosquitoes - Francisco Espinoza-Gómez; Alejandro U. López-Lemus; Irám P. Rodriguez-Sanchez; Margarita L. Martinez-Fierro; Oscar A. Newton-Sánchez; Edgar Chávez-Flores; Iván Delgado-Enciso (Archives of Virology, 2011)

Use of partition and redistribution indexes for heavy metal soil distribution after contamination with a multi-element solution - Patricia Miretzky; Monica Rodriguez Avendaño; Carolina Muñoz; Alejandro Carrillo-Chavez (Journal of Soils and Sediments, 2011)

The Holocene volcanic history of Gran Canaria island: implications for volcanic hazards - Alejandro Rodriguez‐Gonzalez; Jose L. Fernandez‐Turiel; Francisco J. Perez‐Torrado; Alex Hansen; Meritxell Aulinas; Juan C. Carracedo; Domingo Gimeno; Hervé Guillou; Raphaël Paris; Martine Paterne (Journal of Quaternary Science, 2009)
Previous published data, combined with our results of 13 new radiocarbon ages and extensive geological fieldwork, indicate that during the past 11 ka 24 monogenetic basaltic eruptions occurred in the north sector of Gran Canaria. These eruptions can be grouped into three periods of eruptive activity: 1900–3200 14 C a BP; 5700–6000 14 C a BP; and an older period represented by only one eruption, El Draguillo, dated at 10 610 ± 190 14 C a BP. Archaeological studies have shown that the more recent eruptions affected prehistoric human settlements on the island. Field studies demonstrate that the eruptions typically built strombolian cones (30–250 m in height) and associated relatively long lava flows (100–10 350 m in length); a few eruptions also produced tephra fall deposits. The total erupted volume of these eruptions is about 0.388 km 3 (46.1% as tephra fall, 41.8% as cinder cone deposits and 12.1% as lava flows). The relatively low eruption rate (∼0.04 km 3 ka −1 ) during the past 11 ka is consistent with Gran Canaria's stage of evolution in the regional volcano‐tectonic setting of the Canary Archipelago. The results of our study were used to construct a volcanic hazards map that clearly delimits two sectors in the NE sector of Gran Canaria, where potential future eruptions would pose a substantial risk for densely populated areas. Copyright © 2009 John Wiley & Sons, Ltd.

Prevalence of BRCA1 and BRCA2 mutations in breast cancer patients from Cuba - Rolando Comacho Rodriguez; Antonio Alejandro Esperon; Ramon Ropero; Maria Caridad Rubio; Ronald Rodriguez; Rosa M. Ortiz; Juan J. Lence Anta; Mario de los Rios; Deyanira Carnesolta; Maria C. del Olivera; Somalia Stiu Vansam; Robert Royer; et al. (Familial Cancer, 2008)

Effect of domestic processing on bioactive compounds - Alejandro Ruiz-Rodriguez; Francisco R. Marín; Aurelio Ocaña; Cristina Soler-Rivas (Phytochemistry Reviews, 2008)

Polymorphism in the Matrix Metalloproteinase-2 Gene Promoter is Associated with Cervical Neoplasm Risk in Mexican Women - Luz M. Baltazar-Rodriguez; Aristoteles Anaya-Ventura; Maricela Andrade-Soto; Elisa A. Monrroy-Guizar; Jose R. Bautista-Lam; Gregorio Jonguitud-Olguin; Friedman R. Cepeda-Lopez; Veronica A. Centeno-Aguilar; Nelida A. Gonzalez-Hernandez; Alejandro D. Soriano-Hernández; Mario Ramirez-Flores; Angel Lugo-Trampe; et al. (Biochemical Genetics, 2008)

RESIGHTINGS AND BEHAVIOR OF FALSE KILLER WHALES ( PSEUDORCA CRASSZDENS ) IN COSTA RICA - ALEJANDRO ACEVEDO‐GUTIÉRREZ; BERNARD BRENNAN; PATRICIA RODRIGUEZ; MOLLY THOMAS (Marine Mammal Science, 1997)

Experimental release of an Iberian lynx (Lynx pardinus) - Alejandro Rodriguez; Luis Barrios; Miguel Delibes (Biodiversity and Conservation, 1995)